ANALISIS KEMAMPUAN PEMECAHAN MASALAH UNTUK MATERI HIMPUNAN PADA SISWA SEKOLAH MENENGAH PERTAMA - Marta Aurelia Pati; Maria Goretty Diciloam Bantas; Yasinta Yenita Dhiki (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to analyse the problem-solving ability of grade VII students of SMPN 1 Alok Timur Watugong in completing test questions about the set based on polya procedures. The stages of problem-solving according to Polya are understanding the problem, problem-solving plan, executing the plan, and re-examining. This type of research is descriptive qualitative. The instrument used in this study was to provide tests and interviews with students selected for analysis. Data analysis through the stages of data collection, data reduction, data display and conclusion drawing. Based on the results of the study (1) at the stage of understanding the problem from 25 students, there are already 14 students who can understand well and there are 11 students who do not write down what is known and asked (2) at the problem-solving plan stage there are 13 students who do not write down the problem plan (3) at the stage of implementing the plan there are 10 students who do not do because they are not careful in reading the questions (4) at the stage of re-examining there are 16 students who have not reached the stage.